Multitemporal C-band radar measurement on rice fields - Lim, Ka-Sing; Tan, Chue-Poh; Koay, Jun-Yi; Koo, Voon-Chet; Ewe, Hong-Tat; Lo, Yew-Chiong; Azmah Ali, (PIERS, 2007)
This paper investigates the relationship between C-Band backscatter measurement on the physical structure of rice fields and its growth stages. The study is based on a ground-based scatterometer experiment conducted on rice fields at Sungai Burung site in Malaysia for the year 2005 growing season. Seven C-band scatterometer acquisitions at full polarization, namely Horizontal-Horizontal, Horizontal Vertical, Vertical-Horizontal, Vertical-Vertical polarization with incidence angle from 0 degrees to 60 degrees, were measured. At the same time, ground truth data for an entire rice growing season were obtained at 12-day intervals from September to December 2005. The dates were chosen so as to coincide with RADARSAT-1 image acquisitions. The paper describes the experiment and investigates the radar sensitivity to the physical structures of rice at different polarization and incident angles for different rice growth stages. Based on the result, a close agreement of backscattering coefficient between the scatterometer and RADARSAT-1 was obtained.